Raba jezika v upravnih postopkih – med teorijo in prakso - Kovač, Polonca (Slavia Centralis, 2020)
Language use in administrative procedures – between theory and practiceLanguage is an important element of protection of the parties’ rights in administrative procedures, hence the constitutional protection of representatives of the Italian and Hungarian minorities, persons with disabilities, and foreigners is guaranteed. This article focuses on the analysis of legal regulation and the practice of language use in administrative procedures. Drawing from various sources (case law, inspectorate’s reports, Administrative Consultation Wiki web portal, and the survey among the heads of administrative units), the results of the analysis of administrative practice reveal that except for foreigners’ rights, no major issues occur when implementing general (Administrative Procedure Act) or sector specific legislation. Therefore, we suggest for the future merely improvements in terms of legal drafting technique, while a systematic and focused concern for language rights is still required by enhancing the awareness of the officials and the general public.
Keywords: language; administrative procedure; protection of rights; procedural law; administrative practice